Mechanical thrombectomy in patients with stroke due to large vessel occlusion in the anterior circulation and low baseline NIHSS score - Andrea M. Alexandre (Journal of Integrative Neuroscience, 2021)
We sought to verify the benefit of mechanical thrombectomy in patients with acute ischemic stroke due to large vessel occlusion in the anterior circulation and low National Institute of Health stroke scale score at presentation. The prospective database of our stroke center was screened for patients with acute ischemic stroke due to large vessel occlusion and a baseline National Institute of Health stroke scale score ≤5 that had undergone mechanical thrombectomy. Outcome measures were the modified Rankin Scale (mRS) score at 90 days, brain bleeding events and death at 90 days. Out of 459 patients, 17 (12 females, mean age 70 ± 14 years) with occlusion of M1 or M2 segment of middle cerebral artery and baseline National Institute of Health stroke scale score ≤5 underwent mechanical thrombectomy. Eight patients (47%) were treated within 6 hours from the onset, 5 (29%) were treated beyond 6 hours, and 4 (24%) were wake-up strokes. Effective mechanical thrombectomy was achieved in 16 patients (94%) and associated with excellent functional outcomes at 3 months (mRS 0–1) in 13 (76%). The asymptomatic brain-bleeding event was observed in one patient 4 days after effective mechanical thrombectomy concerning safety issues. One patient died 1 month after mechanical thrombectomy of a cause unrelated to stroke. Our findings favor a potential benefit of mechanical thrombectomy in patients with stroke due to large vessel occlusion and low National Institute of Health stroke scale score at presentation. These patients may also benefit from a prolonged time window for treatment.